Nutritional Status Among Female Students at SD Negeri 1 Ciloa Kuningan Regency - Hanifah Mardhotillah; Al Rivan Marsyah Dzikri; Akbar Rizkyan Affandy; Andini Hikmatu Diniah; Dwi Putri Andini; Shela Dwi Amaliyanti (International Journal of Health Engineering and Technology, 2025)
Nutritional status in school-age children is an important indicator in the growth and development of the nation’s next generation that affects academic achievement and productivity in the future. This study aims to determine the nutritional status of female students at SD Negeri 1 Ciloa, Kuningan Regency. This descriptive study was conducted in May 2025 using a total sampling method on all 37 female students. Nutritional status was determined based on the anthropometric index BMI/A through measurements of body weight and height. Data were analyzed univariately using SPSS 24.0. The results of the study showed that 75.7% of female students had good nutritional status, 13.5% were overweight, 8.1% were underweight, and 2.7% were obese. This study identified the phenomenon of a double burden of malnutrition with the simultaneous discovery of malnutrition and overweight problems. Although the majority of female students have good nutritional status, a comprehensive nutritional intervention program is needed thorugh balanced nutrition education, provision of nutritious food in schools, and regular monitoring of nutritional status involving cross-sectoral collaboration to optimize the nutritional status of school-age children. Keywords: Nutritional Status, Malnutrition, Overweight, Obese, School Age Children